Extractive industries, price shocks and criminality - Axbard, S; Benshaul-Tolonen, A; Poulsen, J (University of Oxford, 2019)
A large literature has highlighted the potential detrimental effects of natural resource wealth on social, economic and political outcomes. We study a previously largely unexplored relationship - the impact of natural resource wealth on criminal activity. Our empirical strategy exploits price fluctuations in 15 internationally traded minerals to study the impact of mineral wealth on local crime levels in South Africa - leveraging detailed crime data from 1,084 police precincts over 10 years. We find that increased mineral wealth leads to a reduction in criminal activity. An exploration of mechanisms suggest that the effect is due to changes in employment opportunities created by the mining industry, affecting the opportunity cost of engaging in criminal activity. Consistent with this we also document that results are driven by property crime and that mines are less likely to close down when prices are high. Our results suggest that downward shifts in international mineral prices can cause surges in crime. To investigate how resilience against such surges can be achieved, we exploit the roll-out of a government employment guarantee program and document that the program reduces the crime response to changes in international mineral prices.